The “invisible light”: Tracing its journey from scientific history to physics teaching - Acioly, Vitor; Moreira, Ildeu (Momentum: Physics Education Journal, 2024)
The history of science in teaching has been the subject of much discussion, analysis, practices and educational evaluations in recent decades. The objective is to present an important historical process of physics in the 19th century and to discuss its use and contribution to the understanding of the electromagnetic spectrum. The first part of the work describes the main experiments that led to the confirmation of the existence of 'invisible light', that is, radiations in the infrared and ultraviolet range. The second part explores how one of the original experiments concerning infrared radiation can be used to demonstrate and discuss the existence of radiation outside the visible spectrum. The proposal of the work is that these two dimensions, the historical approach and the accomplishment of pertinent experiments, are concatenated in the didactic exploration of this important content: the meaning of the unified electromagnetic spectrum and its important applications in people's daily lives.